From infancy and beyond… ensuring a lifetime of hepatitis B virus (HBV) vaccine-induced immunity. Issue 8 (3rd August 2018) - Osiowy, Carla
ABSTRACT: Despite the long-term efficacy and immune persistence observed following HBV vaccination of infants, the need for a booster dose following infant immunization continues to be deliberated. Evidence from HBV booster dose response studies and long-term immunization program reviews are the basis for the recommendation that a vaccine booster is not necessary. However, further studies continue to emerge and highlight the need for standardization among observational studies in order to appropriately compare outcomes. There is an assumption that neonatal and infant (within 12 months of age) vaccine immune responses are equivalent; however, evidence exists for distinct vaccine responses within the first year of life. HBV vaccine programs have evolved over time, particularly regarding the type and dosage of vaccine used. Several universal neonatal immunization programs initially incorporated a 2.5 μg dosage (Recombivax-HB, Merck). This dosage has been shown in multiple long-term studies and meta-analyses to be associated with a lower primary response, decreased antibody persistence over time, and a reduced booster response 10 to 20 years following immunization. Ongoing surveillance of this and other HBV neonatally-vaccinated populations, particularly in low endemic regions, is necessary to understand the impact on long-term protection in order to ensure lifelong protection against hepatitis B infection.